A DESCRIPTION OF THE GROWTH IN WEIGHT AND LENGTH OF INFANTS AGED 0-6 MONTHS WHO WERE GIVEN BREAST MILK AND ADDITIONAL FOODS AT THE RAWASARI PUBLIC HEALTH CENTER IN JAMBI CITY - Karoba, Arlina; meinarisa, ica; Nurlinawati, Nurlinawati (Program Studi Keperawatan Universitas Jambi, 2025)
The age of babies under six months is a golden period that can be realized if during this period the baby gets the appropriate nutritional intake for optimal growth and development. The purpose of this study is to determine the description of the growth of body weight and body length of babies aged 0-6 months who are given breast milk and additional food at the Rawasari Community Health Center, Jambi City. Using a descriptive quantitative method. The sampling technique used Quota Sampling with 15 respondents who were exclusively breastfed and 15 babies who were not exclusively breastfed. The results of the study The description of the weight of babies aged 0-6 months who were exclusively breastfed were in the undernutrition and overnutrition categories of 1 respondent each (7%) and the good nutrition category was 13 respondents (86%), The description of the weight of babies who were non-exclusively breastfed were in the good nutrition category of 10 respondents (67%), the overnutrition category was 4 respondents (26%), the undernutrition category was 1 respondent (7%), The description of the length of babies aged 0-6 months who were given exclusive breastfeeding and non-exclusive breastfeeding at the Rawasari Health Center had the same results, namely the short category of 1 respondent (7%) with the normal category of 14 respondents (93%). It can be concluded that babies who are given additional food at the age of 0-6 months can make babies become overweight or obese. Suggestions The results of this study can be a source of information for mothers so that they can provide nutrition to their children at the right time or age.